INTERNALIZATION OF THE CONCEPT OF MONDOK TO RECITE AND BUILD AKHLAKUL KARIMAH IN FILTERING THE CAPITALIZATION OF ISLAMIC EDUCATION - Zainul Arifin; Amyadi Amyadi (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The purpose of this study explains The concept of mondok to recite and build akhlakul karimah in filtering capitalization of Islamic education in Pesantren. This research uses the method qualitatively descriptive with case study type. As for data collection techniques that Used are observation, documentation and depth-interview. This study using Miles and Huberman's interactive model, namely; data reduction, data presentation, drawing conclusions. In testing the validity of the data, researchers use triangulation, namely source triangulation, method triangulation, peer discussion and member check. The results of this study are; The Concept of Mondok for Reciting and Building Akhlakul Karimah is an affirmation of the orientation of Islamic education that leads to a continuous process of humanization, transcendental and liberation and presupposes a continuous learning process until death and is oriented towards the construction of good morals to Allah SWT, to Nature and fellow creatures. The concept of Mondok for Reciting and Building Akhlakul Karimah can filter the orientation of Islamic education with material paradigms such as looking for diplomas, expecting a good career and work through education and leading to improving worldly goodness, but can instill values devotion and faith. Internalization of the concept of mondok to recite and build akhlakul karimah in filtering the capitalization of Islamic education with Learning To Know, Learning to do, Learning to live together, Learning to be. Learn how to learn, learn throught out life. learning to improve, learning to moderate, learnin to evaluate. And learning to do value.